Diagnosis and treatment of hepatic lipidosis in a 42-year-old gray parrot: A case report - Salavati , Ali; Talebi , Zahra; Mahdipour, Maryam; Shojaei, Iman; Peighambari, Seyed Mostafa (Journal of Poultry Sciences and Avian Diseases, 2023)
The African grey parrot (Psittacus erithacus) is among the world's most well-known seed-eating cage birds. A grain-eating diet has been reported to cause liver lipidosis in parrots. Fatty liver syndrome occurs when the liver cannot metabolize and re-secrete processed fatty acids due to excessive dietary fatty acids or lipolysis. The present study involves a 42-year-old African grey parrot with extensive feather pecking in the neck, legs, and chest areas, red color changes in the feathers on the legs, and lethargy. The patient's medical history includes the consumption of sugar, chocolate, and whole grains, which is the main reason for metabolic disorders. A comprehensive evaluation of serum biochemistry, total protein levels, aspartate aminotransferase (AST), creatine kinase (CK), triglycerides, and uric acid was conducted on the first visit. Following two weeks of treatment, the bird was again referred to the clinic for clinical pathological evaluation and diagnostic imaging. Different liver medicines, such as herbal antioxidants, vitamins, and amino acid supplements, are prescribed during the treatment process. In addition, the bird's diet was modified. Following the diet and treatment, the blood parameters reached normal limits. The echogenicity of liver tissue was close to normal after the initial observation of feathers regrowing in some areas, as well as blood sample evaluation. A paraclinical test was taken on the bird again after two months of treatment to ensure the disease did not recur. Diligent care, nutritional support, veterinary monitoring, and appropriate medications can improve hepatic lipidosis, but permanent damage may occur. Therefore, it is very critical to quickly diagnose and prevent the recurrence of the illness.